Through a Critical Lens: Expertise in Epidemiology for and by Indigenous Peoples. (November 2020) - Prussing, Erica
Epidemiology for and by Indigenous peoples uses quantitative and statistical methods to better document Indigenous health concerns, and is oriented around providing data for use in advocacy to promote Indigenous health equity. This advocacy-oriented, technoscientific work bridges the often distinct social worlds of Indigenous communities, professional public health research, and public policy-making. Using examples from a multisited ethnographic study in three settings (Aotearoa New Zealand, Hawai'i, and the continental United States), this paper examines the forms of expertise that researcher/practitioners enact as they conduct research that simultaneously harnesses epidemiology's persuasive power in social worlds like public health and public policy, while also critically challenging legacies of colonialist erasures and misrepresentations of Indigenous health in population statistics. By demonstrating how these continual translations across multiple social worlds enact expertise, this analysis offers a new integration of discussions about both coloniality and expertise within science and technology studies (STS). By focusing on the experiences of technoscientific professionals themselves, this study's findings also pose new questions for broader STS conversations about how activism is shaping the production of knowledge about health in the twenty-first century.